Pengaruh Akuntabilitas, Transparansi, dan Kompetensi Aparatur Desa terhadap Kualitas Laporan Keuangan Desa: Studi pada Desa di Kecamatan Sukaraja, Kabupaten Sukabumi - Aulia Indriani Rahayu; Elan Eriswanto; Sulaeman Sulaeman (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The quality of village financial reports is one form of village government accountability in financial management, which requires the implementation of accountability, transparency, and the competence of village officials to ensure that the financial information produced is reliable and beneficial for stakeholders. This study aims to analyze the effect of accountability, transparency, and the competence of village officials on the quality of village financial reports in villages within Sukaraja District, Sukabumi Regency. This study employed a quantitative method with descriptive and associative approaches. The research data were collected through questionnaires distributed to 54 respondents selected using purposive sampling techniques and analyzed using multiple linear regression analysis with the assistance of IBM SPSS Statistics version 27. The results indicate that accountability, transparency, and the competence of village officials influence the quality of village financial reports both partially and simultaneously. Furthermore, these three variables explain 78.6% of the variation in the quality of village financial reports, while the remaining 21.4% is influenced by other factors outside this study. The findings of this study are expected to serve as a consideration for village governments in improving the quality of village financial reports through strengthening accountability, transparency, and the competence of village officials.